Pemanfaatan Kebun Sayuran Sekolah sebagai Media Pembelajaran dalam Meningkatkan Produktivitas Peserta Didik di SDN Bulusidokare Sidoarjo - Wati, Evi Indar; El-Yunusi, Muhammad Yusron Maulana (Indo-MathEdu Intellectuals Journal, 2024)
Vegetable garden does not only serve as a source of food but also as an educational tool that supports experiential learning. This research was conducted at Bulusidokare Sidoarjo Public Elementary School. Through gardening activities, students can develop practical skills, an understanding of the plant life cycle, and environmental values. This research aims to explore the utilization of vegetable gardens as an innovative learning medium to enhance student productivity. This research method uses a qualitative approach by conducting interviews with teachers and students, field observations, and collecting supporting documentation. The author describes the findings as data analysis. The research results show that student involvement in gardening activities can enhance motivation, teamwork skills, and a sense of disciplined responsibility. In addition, this experience strengthens the understanding of scientific and environmental concepts, as well as enhances the love for nature. Thus, vegetable gardens can be used as an effective learning medium to enhance the productivity and quality of students' education.